The economic collapse of Russia - Bracho C., Gerando; Lopez G., Julio (PSL Quarterly Review, 2012)
The objective of the paper is to contribute to an explanation of Russia's economic decline during its transition to capitalism. The authors argue that, to an important degree, the dismal performance of the Russian economy stems from the overall vision underpinning the transition to capitalism, and to the specific economic policies emanating from that vision. The paper gives first an account of the basic facts regarding Russia's economic depression in the 1990s, followed by the authors' understanding of some of the main economic policies applied, stressing important peculiarities generally overlooked in most studies. The third section analyzes the impact of some of the main economic policies of the Russian transition and ponders whether better alternatives existed. The fourth section briefly assesses the return of economic growth from 1999 onwards. The last section presents conclusions. JEL Codes: E65, O52, P21, P24, P27